Promotion signaling, discrimination, and positive discrimination policies - Oliver Gürtler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The current paper studies discrimination in a model in which promotions are used as signals of worker ability. The model can account for both statistical and taste-based discrimination. A positive discrimination policy lowers the promotion standard for the workers who are discriminated against. This is beneficial for the workers in the middle of the ability distribution because these workers are promoted if and only if the policy is in place. Instead, workers of either high or low ability generally suffer from the policy because the policy does not change their promotion probability but weakens the positive signal of being promoted and strengthens the negative signal of not being promoted. We also show that the policy may increase or decrease efficiency and that it may aggravate wage inequality.
Keywords: J31; J78; M51; 330